2015
DOI: 10.1530/eje-15-0151
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine dose adjustment in hypothyroid women achieving pregnancy through IVF

Abstract: Objective: About one out of two women with primary hypothyroidism has to increase the dosage of exogenous levothyroxine (L-T 4 ) during pregnancy. Considering the detrimental impact of IVF on thyroid function, it has been claimed but not demonstrated that L-T 4 dose adjustment may be more significant in hypothyroid women who become pregnant after IVF. Design: Retrospective cohort study. Methods: Hypothyroid-treated women who achieved a live birth through IVF were reviewed. Women could be included if thyroid fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Women already treated with levothyroxine (LT4) should adapt the dose of LT4 at least 4 weeks before OS. Women with (subclinical) hypothyroidism should initiate LT4 to keep serum TSH levels <2.5 mIU/L [10].…”
Section: Introductionmentioning
confidence: 99%
“…Women already treated with levothyroxine (LT4) should adapt the dose of LT4 at least 4 weeks before OS. Women with (subclinical) hypothyroidism should initiate LT4 to keep serum TSH levels <2.5 mIU/L [10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 26 ]. These inconsistent conclusions may be attributable to the different time windows in which thyroid function testing was conducted and LT4 supplementation was initiated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, confounding by indication may be driving some of the observed associations between fertility drugs and ovarian cancer. This may also be the case for thyroid cancer as, it has been demonstrated that thyroxin substitution treatment is used more frequently by ART pregnant women, than by those pregnant after natural conception (69). It may therefore be that the preexisting thyroid disease may be a common cause of both infertility and thyroid neoplasms.…”
Section: Discussionmentioning
confidence: 99%